Pembinaan dan Penyuluhan terhadap Kader tentang Pengelolaan Posyandu Di Posyandu Cempaka Putih Desa Kolot Kelurahan Linggasari Kecamatan Ciamis (ABDIMAS: Jurnal Pengabdian Masyarakat, 2019)
IHC is one form of community-sourced health efforts (UKBM) managed from, by, for and with the community, to empower the community and provide facilities for the community to obtain basic health services. Efforts to improve the role and function of IHC are not merely the responsibility of the government, but all components in the community, including cadres. The role of cadres in the implementation of IHC is very large because in addition to being a provider of health information to the community to come to the IHC and carry out clean and healthy life behaviors. Linggasari is one of the villages in Ciamis Sub-District, Ciamis Regency, which has good potential about the existence of IHC. The number of IHC in Linggasari Village are 8 units. Cempaka Putih is one of the IHC in Linggasari Village. The IHC is still in progress, which requires assistance. Based on the situation, it is necessary to have assistance for the development of it by conducting community service, namely through fostering and counseling cadres on the management of IHC that is carried out from November 27, 2017 to January 03, 2018.